2003
DOI: 10.1046/j.1365-313x.2003.01864.x
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric approach for identifying putative plasma membrane proteins of Arabidopsis leaves associated with cold acclimation

Abstract: SummaryAlthough enhancement of freezing tolerance in plants during cold acclimation is closely associated with an increase in the cryostability of plasma membrane, the molecular mechanism for the increased cryostability of plasma membrane is still to be elucidated. In Arabidopsis, enhanced freezing tolerance was detectable after cold acclimation at 28C for as short as 1 day, and maximum freezing tolerance was attained after 1 week. To identify the plasma membrane proteins that change in quantity in response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
182
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(195 citation statements)
references
References 70 publications
(80 reference statements)
10
182
1
2
Order By: Relevance
“…Interestingly, by coimmunoprecipitation studies after UV-B treatment followed by the identification of proteins associated to RPL10 in Arabidopsis, we demonstrated that RPL10s associate with proteins involved in the response to pathogens, including transcription factors, suggesting that at least one RPL10 isoform may also have a role in biotic stress (Falcone Ferreyra et al, 2010a). Moreover, RPL10B has also been involved in cold acclimation in Arabidopsis (Kawamura and Uemura, 2003). Collectively, these findings indicate that RPL10B may participate in responses against different stress conditions.…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, by coimmunoprecipitation studies after UV-B treatment followed by the identification of proteins associated to RPL10 in Arabidopsis, we demonstrated that RPL10s associate with proteins involved in the response to pathogens, including transcription factors, suggesting that at least one RPL10 isoform may also have a role in biotic stress (Falcone Ferreyra et al, 2010a). Moreover, RPL10B has also been involved in cold acclimation in Arabidopsis (Kawamura and Uemura, 2003). Collectively, these findings indicate that RPL10B may participate in responses against different stress conditions.…”
Section: Discussionmentioning
confidence: 75%
“…We found the lipocalin-like protein particularly intriguing, because it was not regulated in salt-stressed or osmotically stressed Arabidopsis (Kilian et al, 2007), whereas other members of this gene family are stress responsive, especially under low temperatures (Frenette Charron et al, 2005). Lipocalins are most likely localized in the plasma membrane (Kawamura and Uemura, 2003), bind small hydrophobic ligands, act as transporters, and protect plants from oxidative stress (Frenette Charron et al, 2002;Charron et al, 2008). We used loss-of-function mutants of Arabidopsis to test the involvement of TIL and SIS, a salt-regulated unknown gene in salt tolerance.…”
Section: Stress Acclimation Involves a Redirection Of Protein Metabolmentioning
confidence: 92%
“…These results correlate with previous reports that Arabidopsis BAGs function in cytoprotection. Therefore, AtBAG7 is localized within the ER and is involved in plant PCD pathways, particularly in response to abiotic stress (5,33).…”
Section: Atbag7 Is Involved In Maintenance Of the Unfolded Protein Rementioning
confidence: 99%